Archival research considerations for CRSP data. Issue 3 (3rd September 2018) - Francis, Rick N.; Mubako, Grace; Olsen, Lori
Abstract : Purpose: This study aims to remind researchers that measurement errors and inappropriate inferences may result from improperly combining and adjusting certain Center for Research in Security Prices (CRSP) measures. Design/methodology/approach: In addition to real-world working examples, the study uses earnings announcements data to examine the effects of improperly combining and adjusting CRSP measures. Findings: This study assists researchers with the following two considerations when using CRSP data: stand-alone share prices adjusted with CRSP adjustment factors are inaccurate in the presence of property dividend, spin-off and rights offering events; and ignoring covertly missing stock returns may create misleading test results. The primary objectives of the study are to help researchers increase the integrity of their studies and the probability of publication. Research limitations/implications: Inadequate consideration for the two issues discussed in the paper may change the researcher's statistical inferences. Originality/value: Archival researchers who overtly address and discuss the existence of these issues achieve two important and related benefits. First, the researcher increases his or her credibility with editors and reviewers, which enhances the probability of a published study. Second, the researcher increases his or her perceived technical competency, which potentially affects promotion and tenure decisions, editorial membership decisions, co-authorship opportunities and other professional effects. Doctoral students will find this study to be particularly useful.